Sustainable Tourism Development in Koh Yao Yai, Pang-Nga, Thailand - Witchayakawin, Pakin (IJRDO - Journal of Social Science and Humanities Research, 2017)
This research aims to study tourism management by Koh Yao Yai community, to study perception of visitors on sustainable tourism and to suggest the appropriate method to develop the island to be sustainable site. This qualitative research builds a sample by extremely cases and maximum variation sampling with target group including leaders 15, villagers 40 and visitors 20 subjects. The data were collected during July 2016 by observation, structured interview and focus group discussion. The data analyzing process involved preparing, segmenting, coding, categorizing and themetizing. The results presented the nature is plentifully including forests and beaches. The community participation in management of tourist attractions includes 1) households self-manage garbage by burning and sanitary landfill closuring 2) community cooperates with municipality’s garbage truck to separate and manage garbage in bin or bag as well as to co-operate cleaning beaches 3) villagers participate to preserve nature by tree planting along road and mangrove forest, zoning seagrass, and conserving heredity of sea animals and sea plant 4) community keeps well ways of life, believe and career to show the visitors, and 5) villagers participate to clean the island on big cleaning day each month. Visitors perceived that voyage to Koh Yao Yai is convenient by many boat, enough infrastructure as shops and restaurants. There was garbage in some area but the entire island was cleaned. The island has good ecosystem and there was not serious tourism impacts on nature and economic impact by income increasing. Primary visitors did not join sustainability activities. Locals served them at restaurant and provided rental transport services. There was not souvenir central market while locals expressed welcome and safety feeling. Visitors and villagers stayed together with happiness. Koh Yao Yai should set up a conservation center and manage the wastewater, garbage separation system and add more glossary shops and homestays. The communities should more involve Koh Yao Yai by participation in decision-making and tourist attractions planning. This island should be set up as national park and limit number of tourists.